2012
DOI: 10.1007/s00027-012-0274-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of winter phenology in shaping the ecology of freshwater fish and their sensitivities to climate change

Abstract: Thermal preference and performance provide the physiological frame within which fish species seek strategies to cope with the challenges raised by the low temperatures and low levels of oxygen and food that characterize winter. There are two common coping strategies: active utilization of winter conditions or simple toleration of winter conditions. The former is typical of winter specialist species with low preferred temperatures, and the latter is typical of species with higher preferred temperatures. Reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
260
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(268 citation statements)
references
References 202 publications
6
260
1
1
Order By: Relevance
“…For example, spring spawning fishes could spawn earlier with shorter, warmer winters [32]. In fact, it is increasingly recognized that understanding the seasonal variability in climate change effects may be important when attempting to understand current dynamics and for predicting effects under future scenarios, particularly in fish and wildlife populations [33]. For example, Kanno et al [34] found that seasonal patterns in air temperature and precipitation, both of which are predicted to change under climate warming, were important drivers of survival and reproduction of eastern brook trout.…”
Section: Effects On Fish and Fish Habitatmentioning
confidence: 99%
“…For example, spring spawning fishes could spawn earlier with shorter, warmer winters [32]. In fact, it is increasingly recognized that understanding the seasonal variability in climate change effects may be important when attempting to understand current dynamics and for predicting effects under future scenarios, particularly in fish and wildlife populations [33]. For example, Kanno et al [34] found that seasonal patterns in air temperature and precipitation, both of which are predicted to change under climate warming, were important drivers of survival and reproduction of eastern brook trout.…”
Section: Effects On Fish and Fish Habitatmentioning
confidence: 99%
“…As many species rely on a combination of photoperiod and thermal cues as triggers for critical life history events (e.g., spawning, larval emergence), changes in ice cover phenology may produce detrimental ecological mismatches [65]. For example, fall spawning fish species may be vulnerable to a warmer incubation period, promoting earlier spring hatching and potential starvation if the spring production pulse is not similarly responsive [67]. During warmer, longer summers, cold-water species will be increasingly squeezed between warming surface waters and deep anoxic habitats [67].…”
Section: Implications For Losing Lake Icementioning
confidence: 99%
“…For example, fall spawning fish species may be vulnerable to a warmer incubation period, promoting earlier spring hatching and potential starvation if the spring production pulse is not similarly responsive [67]. During warmer, longer summers, cold-water species will be increasingly squeezed between warming surface waters and deep anoxic habitats [67]. As winter conditions become less severe, aquatic communities will shift from being dominated by winter specialists to species that thrive in warmer, brighter, and more productive environments [4,67].…”
Section: Implications For Losing Lake Icementioning
confidence: 99%
See 1 more Smart Citation
“…The loss of vegetated littoral habitat and/or the increased availability of prey during winter drawdown can cause increased daily movement of largemouth bass (Rogers and Bergersen 1995), which are normally quiescent during the winter (Shuter et al 2012). In contrast, reduced winter water levels show negligible effects on movement behavior in Esox lucius (northern pike), an active winter species (Rogers and Bergersen 1995).…”
Section: Movement and Habitat Usementioning
confidence: 99%